Serum bile acid patterns are associated with the presence of NAFLD in twins, and dose‐dependent changes with increase in fibrosis stage in patients with biopsy‐proven NAFLD. Issue 2 (2nd December 2018) - Caussy, Cyrielle; Hsu, Cynthia; Singh, Seema; Bassirian, Shirin; Kolar, James; Faulkner, Claire; Sinha, Nikhil; Bettencourt, Ricki; Gara, Naveen; Valasek, Mark A.; Schnabl, Bernd; Richards, Lisa; et al.
Summary: Background: The fasting‐state serum bile acid profile in nonalcoholic fatty liver disease (NAFLD) has been reported to differ when nonalcoholic steatohepatitis is compared to nonalcoholic fatty liver. However, there are few data comparing changes in NAFLD vs non‐NAFLD, or whether the bile acid profile differs according to the degree of fibrosis. Aim: To examine the serum bile acid profile across the entire spectrum of NAFLD. Methods: We performed a cross‐sectional analysis of two complementary cohorts: a Twin and Family cohort of 156 participants, and a biopsy‐proven‐NAFLD cohort of 156 participants with fasting bile acid profiling using liquid chromatography/mass spectrometry. Results: In the Twin and Family cohort (mean age 46.3 years and body mass index (BMI) 26.6 kg/m 2 ), 36 (23%) participants had NAFLD (magnetic resonance imaging proton density fat fraction ≥ 5%). Higher chenodeoxycholyl conjugates (9.0% vs 6.5%, P  = 0.019) and lower glycohyocholate (1.2% vs 3.6%, P  < 0.001) were observed in NAFLD compared to non‐NAFLD‐controls. In the biopsy‐proven‐NAFLD cohort (mean age 49.8 years, BMI 32.0 kg/m 2 ), no differences in total bile acid were seen between nonalcoholic fatty liver vs nonalcoholic steatohepatitis. The total unconjugated bile acid significantly decreased across nonalcoholic steatohepatitis categories ( P  = 0.044). The distribution of stage of fibrosis was F0: 42.3%, F1: 32.7%, F2: 10.3%, F3: 8.3% and F4: 6.4%. The total serum bile acid increased with increase in fibrosis stage ( P  < 0.001). The primary conjugated bile acid proportion increased ( P  < 0.001) whereas unconjugated bile acid ( P  = 0.006), unconjugated cholyl ( P  < 0.001) and chenodeoxycholyl conjugates ( P  < 0.002) significantly decreased with increase in liver fibrosis stage. Conclusions: Fasting‐state serum bile acid profile alterations are seen across the entire spectrum of NAFLD. The total serum bile acids did not differ significantly between NAFLD vs non‐NAFLD and nonalcoholic fatty liver vs nonalcoholic steatohepatitis, but were significantly perturbed progressively as liver fibrosis increases.